Extraction and purification of β-galactosidase From the liver of local sheep (Journal of the College of Basic Education, 2022)
The study included selecting the best method for extracting beta-galactosidase from the liver of local sheep, among eight methods, and the use of phosphate buffer (0.2 M, pH 7) was the best in extracting the enzyme with a total efficiency of (78898.5) units. The protein content was concentrated using ammonium sulfate (60%) among five methods of concentration (partial purification), and the purification stages were completed using ion exchange and gel filtration on a DEAE - Sephadex A100 column, and then using gel filtration on a sephacryl column (Sephacryl S - 300).As the specific activity reached (3328.8) units / mg of protein, the enzymatic yield was (41.84)%, and the number of purification times was (8.57) times. Then, the purity of the enzyme was confirmed by conducting the electrophoresis process in the absence of protein denaturing materials, as a protein bundle appeared